Systemic Immune Activation and Responses of Irradiation to Different Metastatic Sites Combined With Immunotherapy in Advanced Non-Small Cell Lung Cancer - Wu, Min; Liu, Jie; Wu, Shihao; Liu, Jingru; Wu, Hui; Yu, Jinming; Meng, Xue (Frontiers in Immunology, 2021)
Purpose: Considering the limited data, we aimed to identify the greatest immune activation irradiated site of common metastases and response to immune checkpoint inhibitors simultaneous in non-small cell lung cancer (NSCLC). Methods: 136 patients with advanced NSCLC who had received radiation to a primary or metastatic solid tumor were enrolled. We recorded blood cell counts in three time periods, before, during and after radiotherapy (RT), and derived some blood index ratios including monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII). The delta-IBs were calculated as medio-IBs ÷ pre-IBs－1. We analyzed the changes before and during RT using Spearman rank correlation test, Kruskal-Wallis rank sum test, as well as logistic regression analyzing their correlation with efficacy. Results: The medians of delta-MLR and delta-PLR were both the lowest while the median of delta-L was the highest in brain. Therapeutic effect evaluation showed that the objective response rate (ORR) of 48.65% (18/37) in brain irradiation group was the highest, compared with 17.07% (7/41) in bone and 41.94% (13/31) in lung. Conclusions: In this study, results suggested that irradiation to brain has the best immune activation effect and patient outcome compared with other organs in NSCLC and the earlier-line ICIs was intervened with RT, the better patient outcome was reached. Prospective studies are also necessary to provide more convincible evidence and standards for clinical irradiation metastases selection.